How often is Klippel-Feil Syndrome associated with congential heart disease presentation of five cases and a review of the literature - Bejiqi, Ramush; Retkoceri, Ragip; Maloku, Arlinda; Bejiqi, Rinor; Mustafa, Aferdita; Husremovic, Faruk; Bejic, Samir (Journal of Cardiology and Cardiovascular Medicine, 2019)
Introduction: Klippel-Feil syndrome (KFS), is a bone disorder characterized by the abnormal joining (fusion) of two or more spinal bones in the neck (cervical vertebrae), which is present from birth. Three major features result from this abnormality: a short neck, a limited range of motion in the neck, and a low hairline at the back of the head. In some individuals, KFS can be associated with a variety of additional symptoms and physical abnormalities which contribute in the deterioration and complication of the condition of the child. Aim of presentation: Here, we report five children from Kosovo with KFS associated with different heart abnormalities, clinical presentation, diagnosis, management, and outcomes of selected conditions in resources-limited settings. Methods: Retrospectively we analysed medical reports of five children, diagnosed at different age with congenital disease and clinical and lab signs of Klippel-Feil syndrome. Conclusion: Basing on our cases, all diagnosed in a small country as a Kosovo, we can conclude that KFS is not such a rare condition. In addition, such syndrome is not so rarely associated with different congenital heart disease. In four cases cardiac surgery was indicated and successfully was done abroad Kosovo in the lack of such services in Kosovo.